Communication and interpretation of regional weather forecasts: a survey of the Italian public. (3rd November 2014) - Zabini, Federica; Grasso, Valentina; Magno, Ramona; Meneguzzo, Francesco; Gozzini, Bernardo
Abstract The aim of the present study is to contribute to the correctness and effectiveness of weather forecast communication, the importance of which has been steadily growing along with the improvement in numerical weather prediction models and methods as well as the general awareness about the increase of extreme events within a context of global climate change. An extensive survey was conducted among the general users of the weather forecasts issued by the regional meteorological service of Tuscany, Italy (LaMMA Consortium), which resulted in 2388 volunteers responding to the questions aimed at better understanding of how people access, interpret and use weather forecasts. The survey also includes some items investigated in previous research, allowing comparison with similar findings in other countries. The most critical issue concerns the uncertainty information, investigated with the main aim of verifying the existence and relevance of inferential mechanisms in the interpretation of weather icons and maps used in LaMMA forecasts to assess uncertainty. The present study also discusses users' interpretations of the probability of precipitation forecasts and their preferences on how forecast uncertainty is conveyed. Results show that, even if the Italian public is accustomed to strictly deterministic weather forecasts, people attribute uncertainty to them on their own even if lacking any explicit indication, thus suggesting the need to supplement the existing forecasts with both graphical and textual information about uncertainty, particularly in the case of precipitation forecasts.